2010
DOI: 10.1504/ijmc.2010.032974
|View full text |Cite
|
Sign up to set email alerts
|

Assessing user experiences and usage intentions of m-banking service

Abstract: M-banking is a channel through which banks interact with customers via mobile devices. M-banking is an emerging mobile commerce application. It is a challenging task for banks to encourage customers to continue using m-banking services, and attract new customers to the service. This study clarifies the differences in the thinking paths of users of m-banking services, and consumers who have not yet used m-banking services, in terms of their involvement. We prove that consumers equipped with more product knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…In addition, a few studies (e.g., Akturan and Tezcan, 2012;Masrek et al, 2012;Shih et al, 2010) cite m-banking as an innovative communication channel in that the customer interacts with a bank through a portable device. A product or service offered by a bank or a microfinance institute (bank-led model) or MNO (non-bank-led model) for conducting financial and non-financial transactions using a mobile device, namely a mobile phone, smartphone, or tablet.…”
Section: "Please Insertmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a few studies (e.g., Akturan and Tezcan, 2012;Masrek et al, 2012;Shih et al, 2010) cite m-banking as an innovative communication channel in that the customer interacts with a bank through a portable device. A product or service offered by a bank or a microfinance institute (bank-led model) or MNO (non-bank-led model) for conducting financial and non-financial transactions using a mobile device, namely a mobile phone, smartphone, or tablet.…”
Section: "Please Insertmentioning
confidence: 99%
“…Despite such benefits, the use of mobile phones or tablets to conduct banking transactions or access financial information is not as widespread as might be expected (e.g., Dineshwar and Steven, 2013;Luarn and Lin, 2005;Shih et al, 2010), as demonstrated by popular media reports (e.g., Accenture, 2013). Juniper Research (2013) has revealed that more than 1 billion people are expected to use m-banking globally by 2017, but that level represents only 15% of the global mobile subscription base-a base that accounts for approximately 96% of the world's population (International Telecommunication Union, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The environment of the banking industry is highly uncertain and crisis-prone (Shih, Hung and Lin, 2010). Therefore, it is important for banks to focus on the techniques of knowledge sharing to cope with a changing environment.…”
Section: Introductionmentioning
confidence: 99%
“…Jun and Palacios (2016) described that mobile banking has enabled financial organizations to offer their consumers extremely value-added services, such as reliability, easy to use, enjoyment of service and capability to access monetary services like cash withdraw service, balance inquiry, money transfer service, account information, mobile topup service, and bill payments service and without time and geographical constraints ( Shih et al, 2010). Focusing on m-banking, Thakur (2014) mentioned that the consequence of mbanking is still greater due to the growing focus of financial institutions on mobile device in order to get in touch with a larger group of consumers.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%